2022
DOI: 10.1186/s13102-022-00514-1
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of current concussion identification and diagnosis methods in sports settings: a systematic review

Abstract: Background Concussion in sport is an ongoing global concern. The head injury assessment (HIA) by the field of play is acknowledged as the first step in recognising and identifying concussion. While previous systematic literature reviews have evaluated the sensitivity of side-line screening tools and assessment protocols, no systematic review has evaluated the research designs and assessments used in a field setting. This systematic review investigated existing screening and diagnostic tools use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 50 publications
(87 reference statements)
0
9
0
Order By: Relevance
“…Research has also identified that variables such as exertion [ 13 , 14 ], learning effects [ 15 ], or attention deficit hyperactivity disorder (ADHD) [ 16 ] can have confounding effects on such tools. For these reasons, it is currently advised that a multi-modal assessment such as the Concussion in Sport Group’s (CISGs) Sport Concussion Assessment Tool (SCAT) [ 17 ] be used to better detect SRCs [ 18 ]. However, each of these methodologies requires medical professionals to administer, which can be time-intensive for those not specialized in sports medicine [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research has also identified that variables such as exertion [ 13 , 14 ], learning effects [ 15 ], or attention deficit hyperactivity disorder (ADHD) [ 16 ] can have confounding effects on such tools. For these reasons, it is currently advised that a multi-modal assessment such as the Concussion in Sport Group’s (CISGs) Sport Concussion Assessment Tool (SCAT) [ 17 ] be used to better detect SRCs [ 18 ]. However, each of these methodologies requires medical professionals to administer, which can be time-intensive for those not specialized in sports medicine [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Both (SRC and mTBI) share subjective presentations [ 8 , 9 ] and are often used interchangeably, particularly in the sporting context [ 2 ]. Improvements in technology, education, and concussion identification protocols [ 10 ] have led to an increase in the reporting of SRC incidents [ 11 , 12 ], though many are still going unreported or undiagnosed [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…), which typically have limited medical field side support. This situation increases the risk of SRCs going undetected or undiagnosed and athletes’ exposure to RHIs [ 10 ]. Scullion et al [ 30 ] identified that players and coaches in amateur sports may have limited knowledge and training regarding SRC, in contrast to those in professional or elite team settings [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, there is increasing discussion and emerging evidence of the benefits of utilizing supplementary markers within the concussion assessment protocols [ 8 , 9 , 10 ]. Incorporation of assessments such as eye-movement testing provides objective screening to assist sports club medical staff who may suspect a concussion, or during the recovery phase after a sport-related concussion [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%